Penerapan Metode Talking Stick Untuk Meningkatkan Keaktifan Siswa dalam Pembelajaran IPAS Kelas 5 di SDN 42 Pekanbaru - Novi Astari; Fitriyeni (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to enhance student activeness in IPAS learning through the implementation of the Talking Stick method in fifth-grade students at SDN 42 Pekanbaru. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data were collected through observations, questionnaires, and documentation, then analyzed to determine the level of teacher and student activeness during the learning process. Findings from Cycle I show that student activeness reached the